(untitled) (Signifiances (Signifying), 2019)
The paper shows that after decades of patient research about the signifié and thanks to what it has allowed in the linguistic study of the signifiant, it is necessary to adopt a non-stratified (and non plurisemic) view of the signifié and to describe the signifiant as an association of an external form with an internal one. It therefore describes in detail the reality of plurisemy, the reality of plurimorphy and polymorphy and the way each of these phenomena allows the reinforcement of the other. It thus introduces on the one hand the morpheme/lexeme distinction, the plurisemy of lexemes and prosodic issues, before contrasting non-linear and archiphonemic morphemes and linear and phonemic lexemes.